The US case : what can we learn from it? - Vu, Cung (2022)
For almost two years, more than 200 million people worldwide have been infected with COVID-19 resulting in more than 4.5 million deaths. The US has been playing a critical role in addressing the pandemic. What could one learn from its successes and challenges?